SIMBOL DAN MAKNA RITUAL YAQOWIYU DI JATINOM KLATEN - Nur Islami, Mona Erythrea; Ikhsanudin, Muhammad (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2014)
Yaqowiyu is one syncretism practice that still survives to this day in Indonesia. Ritual held every â€œSaparâ€ evolved since this days of Islamic Mataram. The purpose of the ritual is to remember the great merit of Ki Ageng Gribig, one of the missionaries of Islam in Jatinom Klaten during the reign of the â€œSultan Agung Hanyokrokusumoâ€. Yaqowiyu ritual uniqueness lies in deployment â€œapemâ€ in peak ceremony, which is around cake made of rice flour with coconut pieces in the middle. This research aims to reveal the meaning of Yaqowiyu. Research methods used are observation, life history interviews and historical method is to do an analysis of the documents. The results showed that Javanese people is still strong believe in animism. Yaqowiyu interpreted as a ritual to mantain the safety and peace embodied by the behavior of â€œngalap berkahâ€. â€œApemâ€ cake meant as a tool to realize their request. But on the other hand, Yaqowiyu also be used as a propaganda strategy to spread the religion of Islam. At this point, Yaqowiyu also be interpreted as a tourist commodity that can be sold.